2016
DOI: 10.5194/isprsarchives-xli-b1-953-2016
|View full text |Cite
|
Sign up to set email alerts
|

Unmanned Aerial Vehicle Use for Wood Chips Pile Volume Estimation

Abstract: Commission ICWG I/VbKEY WORDS: Unmanned aerial vehicle, wood chips pile, DJI Phantom, photogrammetry ABSTRACT:The rapid development of unmanned aerial vehicles is a challenge for applied research. Many technologies are developed and then researcher are looking up for their application in different sectors. Therefore, we decided to verify the use of the unmanned aerial vehicle for wood chips pile monitoring. We compared the use of GNSS device and unmanned aerial vehicle for volume estimation of four wood chips … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Since the high accuracy of UAV photogrammetry or oblique photography, many types of research have been conducted. Mokroš et al 1 used poles for scale reference and done monocular 3D reconstruction with a single UAV, obtaining a volume error about 10% between values calculated from global navigation satellite system (GNSS) data under an average reconstruction density of 75; 300 points per m 3 . In the work of Nesbit and Hugenholtz, 3 the steep part of structure from motion reconstruction results from UAVs are enhanced by incorporating oblique images.…”
Section: Uav Photogrammetrymentioning
confidence: 99%
See 1 more Smart Citation
“…Since the high accuracy of UAV photogrammetry or oblique photography, many types of research have been conducted. Mokroš et al 1 used poles for scale reference and done monocular 3D reconstruction with a single UAV, obtaining a volume error about 10% between values calculated from global navigation satellite system (GNSS) data under an average reconstruction density of 75; 300 points per m 3 . In the work of Nesbit and Hugenholtz, 3 the steep part of structure from motion reconstruction results from UAVs are enhanced by incorporating oblique images.…”
Section: Uav Photogrammetrymentioning
confidence: 99%
“…Densely reconstruct the entire pile with oblique photography, photogrammetry, or light detection and ranging (LiDAR) to get the detailed mesh, and then compute the volume of mesh. 1,2 However, these approaches require either intensive human resource or high computational power, causing high time usage in volume calculation. For better illustration, a 11; 500m 3 pile requires more than 3 h to measure with a TST 2 ; for dense reconstruction approaches, a typical landfill base of approximately 53; 628m 2 can take more than 1 day for a modern computer to reconstruct.…”
Section: Introductionmentioning
confidence: 99%
“…Mokroš et al [19] used a commercial low-cost quadcopter (DJI Phantom 3 Professional) to fly at an altitude of ~20 meters in order to estimate the volume of wood chips pile. After comparing the results with the volume resulted with a GNSS (Global Navigation Satellite System) device, the authors concluded that the use of UAVS does not lead to significantly different results (10.4% more volume estimated via drone method) and the time to collect data is significantly lower (12-20 times less) with the advantage of documentation through ortho mosaic [19].…”
Section: Precision Forestry and Sustainable Forest Planning Managementmentioning
confidence: 99%
“…Geodetic ranging poles were used to determine the scale. Agisoft PhotoScan Professional software was used to determine the volume and surface of the woodchip piles [18][19].…”
Section: Materials and Experimental Pilesmentioning
confidence: 99%